INFLUENCE OF BEHAVIORAL RISK FACTORS ON THE STATE OF THE CARDIORESPIRATORY SYSTEM OF GIRLS LIVING IN THE ARCTIC REGION - Klokotova E.A. ,; Varentsova I.A. ,; Pushkin V.N. ,; Fedorova E.Yu. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the effect of tobacco intoxication on the functional state of the cardiorespiratory system in girls from the Arctic region. Methods and structure of the study. The experiment involved 51 girls aged 20.54±1.7 years (girls who use smoking tobacco - n=21; girls who do not use smoking tobacco - n=30). To assess the degree of nicotine addiction, subjects using smoking tobacco filled out the Fagerström test. Results and conclusions. The results of the experiment show that the hemodynamic and pulmonary systems, regardless of the addiction / disinterest in smoking in girls, are preserved. However, the depth of breathing in people who are fond of smoking, in a state of relative muscle rest, is almost 38% less. Performing physical activity provokes a more significant increase in the values of oxygen consumption (O2), CO2, respiratory volume in smoking girls. Also, in this group, it takes more time to restore the respiratory system after exercise, in contrast to non-smoking respondents. It can be assumed that in smoking girls, tobacco intoxication provokes the accumulation of toxic elements in the body and higher rates of gas exchange are required to remove toxic substances.